Pattern recognition receptors from lepidopteran insects and their biological functions. (July 2020) - Lin, Zhe; Wang, Jia-Lin; Cheng, Yang; Wang, Jin-Xing; Zou, Zhen
Abstract: Lepidopteran insects have potent innate immunity to fight against the invading pathogens. As the initiation step, pattern recognition receptors (PRRs) recognize and bind microbial surface configurations known as pathogen-associated molecular patterns (PAMPs). Aftermath, they initiate both cellular and humoral immune responses, including phagocytosis, agglutination, nodulation, encapsulation, prophenoloxidase activation, and synthesis of antimicrobial peptides. In this review, we summarize the recent findings concerning PRRs in lepidoptaeran insects, mostly agriculture pests including Helicoverpa armigera, Plutella xylostella, and Spodoptera exigua . We mainly focus on the function and phylogeny of C-type lectins (CTLs), peptidoglycan recognition proteins (PGRPs), β-1, 3-glucan recognition proteins (βGRPs), and galectins (GALEs). It enriches our understanding of the immune system of lepidopteran insects and provides directions in the future research. Highlights: The CTLs from lepidopteran insects play critical roles in innate immune responses as well as physiological processes. As pattern recognition receptors, the CTLs, PGRPs, βGRPs, and GALEs have been studied in lepidopteran insects. The dual carbohydrate-recognition domains CTLs from lepidopteran insects are involved in the melanization pathway.